Ecological correlates of the distribution limits of two poeciliid species along a salinity gradient. (25th January 2013) - Torres‐Dowdall, Julián; Dargent, Felipe; Handelsman, Corey A.; Ramnarine, Indar W.; Ghalambor, Cameron K.
<x xml:space="preserve">Abstract</x> Identifying the environmental factors responsible for the formation of a species' distribution limit is challenging because organisms interact in complex ways with their environments. However, the use of statistical niche models in combination with the analysis of phenotypic variation along environmental gradients can help to reduce such complexity and identify a subset of candidate factors. In the present study, we used such approaches to describe and identify factors responsible for the parapatric distribution of two closely‐related livebearer fish species along a salinity gradient in the lowlands of Trinidad, West Indies. The downstream distribution limits of Poecilia reticulata were strongly correlated with the brackish–freshwater interface. We did not observe significant phenotypic variation in life‐history traits for this species when comparing marginal with more central populations, suggesting that abrupt changes in conditions at the brackish–freshwater interface limit its distribution. By contrast, Poecilia picta was present across a wide range of salinities, although it gradually disappeared from upstream freshwater localities. In addition, P. picta populations exhibited an increase in offspring size in localities where they coexist with P. reticulata, suggesting a role for interspecific competition. The parapatric distribution of these two species, suggests that P. reticulata distributions are limited by an abiotic factor (salinity), whereas P. picta is limited by a biotic factor (interspecific competition). Similar parapatric patterns have been previously described in other systems, suggesting they might be a common pattern in nature. © 2013 The Linnean Society of London